ASSA14-03-22 Lack of association between PON1 gene polymorphisms and high platelet reactivity in patients undergoing selective coronary stent placement in Chinese Han population. (1st December 2014) - Liu, T; Zhang, X; Zhang, J; Cai, W; Zhang, D; Liang, Z; Yan, C; Han, Y
Abstract : Background: There is a wide variation in the clinical therapeutic activity of clopidogrel, which has mainly been attributed to genetic effects. Recent a study reported that Paraoxonase-1 (PON1) as a key enzyme plays a vital part in clopidogrel bioactivation. The aim of our study was to assess whether PON1 gene polymorphisms are correlation with the low rates of clopidogrel bioactivation and responsible for negative clopidogrel efficacy in patients undergoing selective coronary stent implantation. Methods: A total of 2069 patients undergoing DES placement were enrolled in this study, all the subjects were pre-treatment with 600 mg clopidogrel and post-treatment with 75 mg/day for at least 12 months. Five tagSNPs (the coding polymorphisms Q192R (rs662) and L55M (rs854560); the promoter polymorphisms -108C/T (rs705379), -162A/G (rs705381) and -909G/C (rs854572) of PON1 gene were selected in this study. Genotypes were identified by polymerase chain reaction (PCR) direct sequencing of genomic DNA, and platelet function was assessed by 20 μmol/l ADP-induced platelet aggregation and by flow-cytometric analysis of platelet surface CD62-P and PAC-1 protein expression before and after clopidogrel. In addition, activity level of PON1 towards phenylacetate was measured by at 270 nm using a UV-2550 spectrophotometer. PON1 concentration was measured by human Elisa kit. Results: Among all of the studied polymorphisms, none of these was related to individuals with high platelet reactivity (HPR). The variations of CD62-P, PAC-1 protein expression were not statistically significant in HPR and no-HPR groups (p = 0.258 and p = 0.574, respectively). The mean values for serum PON1 activity and concentration were 98.83 ± 22.02 and 81.48 ± 17.82 for HPR patients and 105.12 ± 27.76 and 90.67 ± 16.33 for no-HPR patients, and no significant differences can be observed in the two groups. Conclusion: Based on these results, no statistically significant difference was detected between PON1 gene polymorphisms and clopidogrel on-treatment platelet reactivity in patients undergoing selective coronary stent placement in Chinese Han population.